Pengaruh Value Product dan Experience Value Terhadap Loyalitas Pelanggan Kinikawa - Suci Ananda Febrianti; Lusi Olis Vera; Lamia Eva Rini; Fitria Azizah; Ummu Artha Tsary Rumalessin (eCo-Fin, 2026)
Customer loyalty plays an essential role in enhancing business performance, especially within the coffee shop industry where competition continues to escalate. This research investigates how Value Product and experiential value influence customer loyalty at Kinikawa Coffee. A quantitative research framework was employed, with data collected from 122 customers through a questionnaire survey. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The bootstrapping results indicate that Value Product has a strong and statistically significant effect on customer loyalty (β = 0.670, p < 0.001). On the other hand, experiential value shows a positive but statistically insignificant relationship with customer loyalty (β = 0.184, p = 0.198). These findings suggest that customer loyalty at Kinikawa is primarily driven by perceived Value Product factors, including product quality, price fairness, and variety range, while experiential factors do not play a decisive role in determining loyalty. This study contributes to the literature on customer loyalty by providing empirical evidence from a local coffee shop context and offers managerial recommendations for coffee shop managers to focus on enhancing Value Product as a key strategy to foster enduring customer loyalty.